2003
DOI: 10.1089/104454903321112505
|View full text |Cite
|
Sign up to set email alerts
|

The Inverted CCAAT Motif is an Indispensable Element of the Enhancer B of the Mouse Major Histocompatibility IH2-KbGene

Abstract: We have identified a strong binding of nuclear proteins derived from Ltk(-) fibroblasts to the enhancer B of the mouse MHC class I H2-K(b) gene. The inverted CCAAT motif and its adjacent upstream sequences have been revealed as protein-binding sites by electrophoretic mobility-shift, methylation interference, and DNase I footprint assays. Specific mutations in the inverted CCAAT motif as well as in the 5'-flanking cytosine pentanucleotide abrogated the formation of the major DNA-protein complex. Transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Some lowmolecular-weight ligands are known to recognize specific DNA sequences and inhibit transcription factor binding and so could be exploited to modulate transcription and block cellular proliferation. 1−8 Nuclear factor Y (NF-Y) is a ubiquitous CCAAT-binding 9 transcription factor comprising three subunits, NF-YA, NF-YB, and NF-YC, and is involved in cell differentiation and cell cycle progression. 10−12 It has been shown that binding of the heterotrimeric NF-Y to five inverted CCAAT boxes (ICBs) within the promoter region of DNA topoisomerase IIα (Topo IIα) results in control of transcriptional expression at confluence, p53-induced down-regulation, and response to heat-shock-induced up-regulation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some lowmolecular-weight ligands are known to recognize specific DNA sequences and inhibit transcription factor binding and so could be exploited to modulate transcription and block cellular proliferation. 1−8 Nuclear factor Y (NF-Y) is a ubiquitous CCAAT-binding 9 transcription factor comprising three subunits, NF-YA, NF-YB, and NF-YC, and is involved in cell differentiation and cell cycle progression. 10−12 It has been shown that binding of the heterotrimeric NF-Y to five inverted CCAAT boxes (ICBs) within the promoter region of DNA topoisomerase IIα (Topo IIα) results in control of transcriptional expression at confluence, p53-induced down-regulation, and response to heat-shock-induced up-regulation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Transcription factor binding sites in disease-related genes are potential therapeutic targets for small molecules. Some low-molecular-weight ligands are known to recognize specific DNA sequences and inhibit transcription factor binding and so could be exploited to modulate transcription and block cellular proliferation. Nuclear factor Y (NF-Y) is a ubiquitous CCAAT-binding transcription factor comprising three subunits, NF-YA, NF-YB, and NF-YC, and is involved in cell differentiation and cell cycle progression. It has been shown that binding of the heterotrimeric NF-Y to five inverted CCAAT boxes (ICBs) within the promoter region of DNA topoisomerase IIα (Topo IIα) results in control of transcriptional expression at confluence, p53-induced down-regulation, and response to heat-shock-induced up-regulation. ,− In mammalian cells, Topo IIα represents one of the most important cellular targets for a range of anticancer drugs . High levels of topoisomerase II gene expression correlate with the relative sensitivity of cells to these agents, while low levels confer drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the direct negative regulation of the swine class I PD1 gene by c‐jun (Howcroft et al ., 1993) could be explained by evolutionary divergence. Differential regulation of the MHC class I genes of various species has been demonstrated, for example with regard to lymphoid specific expression between the H2‐K b and PD1 genes (Weissman & Singer, 1991; Hatina et al ., 1999), the position‐independent expression of the transgene between the H2‐K b and HLA‐B7 genes (Chamberlain et al ., 1991; Drezen et al ., 1992; Hatina et al ., 1999), and the regulatory sequences mediating transcriptional activation of the H2‐K b and PD1 genes by the coactivator CIITA (Jansa & Hatina, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription signals within the 5′ region contain TATAA, CCAAT, and G-C elements [58,65]. One of these elements, a 12-base pair inverted CCAAT repeat, has been established as a transcriptional protein binding site [58,65,66]. The inverted CCAAT motif responsible for transcriptional activation of TK1 is most likely recognized by the transcription factor CCAAT-binding protein CP1 due to sequence homology with other genes regulated by CP1 [4,65].…”
Section: Tk1 Regulation At the Dna Mrna And Protein Levelsmentioning
confidence: 99%